The burden of endometriosis symptoms on health-related quality of life in women in the United States: a cross-sectional study. (2nd October 2017) - Soliman, Ahmed M.; Coyne, Karin S.; Zaiser, Erica; Castelli-Haley, Jane; Fuldeore, Mahesh J.
Abstract: Introduction: To examine the symptomatic burden of endometriosis on health-related quality of life (HRQL) in women in the United States (US). Methods: A cross sectional web-based survey study was conducted among women using survey panels. The survey included study-specific questions and standardized HRQL questionnaires. Participants reviewed a list of endometriosis symptoms and selected all symptoms they had ever or were currently experiencing. For current symptoms, participants rated the severity and bothersomeness of each symptom. Participants completed the endometriosis health profile (EHP-30) core questionnaire. Descriptive analyzes were performed and multivariate regressions were run with each EHP subscale as a dependent variable to examine the impact of symptoms while controlling for age and comorbid conditions. Results: Mean age of the 1269 women was 34.3 ± 0.3; 78% were white. At least 75% reported having ever experienced: pelvic pain/cramping during their menstrual period, anxiety/stress, lower back pain or fatigue/weariness/anemia. EHP-30 scores ranged from 33.6 (95% CI: 31.4, 35.8) (social support) to 37.8 (95% CI: 35.5, 40.1) (control and powerlessness), indicating moderate HRQL impact. For all but one domain and one symptom, EHP-30 scores were significantly higher (worse) for women who had individual endometriosis-related symptoms than for those who did not. EHP-30 scores consistently deteriorated with each increase in the number of symptoms experienced and by increasing perceived disease severity. Pelvic pain/cramping during menstrual period, irregular periods and general abdominal pain were significantly associated with the EHP-30 domain scores in the regression models. Conclusion: Experiencing endometriosis symptoms is associated with lower HRQL. Importantly, as symptom severity and number of symptoms increase, HRQL further deteriorates.